Análise espacial dos atendimentos a crianças e adolescentes vulneráveis no município de Foz do Iguaçu - Bortoli, Dayse Mara (2015)
Understanding the profile of violence against children and adolescents of a given region is essential to implement appropriate public policies focused on this audience. The objective of this study was to Analyze the cases of violation of the rights of children and adolescents occurred in the city of Foz do Iguaçu PR from 2013 to 2014. The data related to the case of violence were obtained through the compulsory violence notification sheet from the Epidemiology Sector and the data of service network were obtained from the Department of Social Services, Family and Relations with Municipal Community of Foz do Iguaçu, Paraná. In the period from 2013 to 2014, there were 578 cases of violation of the rights of children and adolescents, and comprised a greater number of cases of violence against children and predominantly involved females, and the predominant place of occurrence was home. There was a predominance of cases against children involving physical, sexual and psychological violence and neglect, and the Demographic Expansion Areas (AED) that concentrated more recorded cases of violence of different types involving both children and adolescents were the AEDs 1 (Três Lagoas), 3 (Morumbi), 5 (Jd São Paulo) and 11 (Carimã) that are located in the northeast, east and south region of the city, respectively. These regions can be considered regions of the periphery of the city. By contrast the AEDs with fewer reports of violence were the AEDs 6 (Jd America) and 9 (Centro). In the built environment analysis, it was found that the safety net is complete only at AED 9 (center). We conclude that the profile of child and adolescent, victims of violence, and the type of violence suffered, registered in the city of Foz do Iguaçu, during the period 2013-2014, was similar to that found in other national studies. Despite the city of Foz do Iguaçu be in accordance with national guidelines on social services, health and education installed in different areas of the city, the data indicate the need for improvements in existing social assistance network.